2011
DOI: 10.1016/j.bmc.2010.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and serotonin transporter activity of 1,3-bis(aryl)-2-nitro-1-propenes as a new class of anticancer agents

Abstract: Synthesis and serotonin transporter activity of 1,3-bis(aryl)-2-nitro-1-propenes as a new class of anticancer agents, Bioorganic & Medicinal Chemistry (2010), doi: 10.1016/j.bmc.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Previous reports indicated that β-nitrostyrene derivatives exhibited anticancer activities via induction of apoptosis [8, 12, 32]. In agreement with these reports, our current data revealed that colorectal cancer cells treated with CYT-RX20 underwent caspase-associated apoptotic cell death.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports indicated that β-nitrostyrene derivatives exhibited anticancer activities via induction of apoptosis [8, 12, 32]. In agreement with these reports, our current data revealed that colorectal cancer cells treated with CYT-RX20 underwent caspase-associated apoptotic cell death.…”
Section: Discussionsupporting
confidence: 92%
“…β-nitrostyrene derivatives induced pro-apoptotic effect through inhibition of protein tyrosine phosphatases (PTPs) and phosphatases 2A (PP2A) [12,13] and inhibited the growth of cancer cells derived from stomach and immune responses of macrophages [6]. In addition, they induced the apoptosis in Burkitt's lymphoma derived cells via chromatin condensation and membrane blebbing [14]. The potent effects of β-nitrostyrene derivatives on inhibiting the TNFα-induced NF-κB survival pathway in a truncated retinoid X receptor α (tRXRα)-dependent manner resulted in a synergistic effect of β-nitrostyrene derivatives and TNFα on inducing breast cancer cell apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Three of these compounds 56, 62 and 66 also displayed the ability to overcome M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT chemotherapeutic resistance due to drug efflux pumps. However, the significant antiproliferative and apoptotic effects of compound 56 on BL cell lines, together with a lack of toxicity against normal PBMCs suggests this nitrostyrene based compound as a potential lead compound in the development of new anticancer agents and warrants further investigation [43]. These results also demonstrate the importance of defining structureactivity relationships for novel compounds.…”
Section: Resultsmentioning
confidence: 85%
“…The nitrostyrene 62 compound, displayed the most potent activity for the DG-75 cell line with an EC 50 value of 1.5 µM. The potent antiproliferative effect of compound 62 on BL cell lines further suggests nitrostyrene based compounds as potential lead compounds in the development of new anticancer agents [43]. The styrene 49 was found to have no effect on the viability of DG-75 cells (>50 % cell viability at 100 µM), compared to the nitrostyrene 62, which displayed the most potent M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 92%